The things we leave unfinished [large type] - Yarros, Rebecca (Thorndike Press large print dynamic drama., 2026)
"Twenty-eight-year-old Georgia Stanton has to start over after she gave up almost everything in a brutal divorce--the New York house, the friends, and her pride. Now back home at her late great-grandmother's estate in Colorado, she finds herself face-to-face with Noah Harrison, the bestselling author of a million books where the cover is always people nearly kissing. He's just as arrogant in person as in interviews, and she'll be damned if the good-looking writer of love stories thinks he's the one to finish her grandmother's final novel... even if the publisher swears he's the perfect fit. Noah is at the pinnacle of his career. With book and movie deals galore, there isn't much the "golden boy" of modern fiction hasn't accomplished. But he can't walk away from what might be the best book of the century--the one his idol, Scarlett Stanton, left unfinished. Coming up with a fitting ending for the legendary author is one thing, but dealing with her beautiful, stubborn, cynical great-granddaughter, Georgia, is quite another. But as they read Scarlett's words in both the manuscript and her box of letters, they start to realize why Scarlett never finished the book--it's based on her real-life romance with a World War II pilot, and the ending isn't a happy one. Georgia knows all too well that love never works out, and while the chemistry and connection between her and Noah is undeniable, she's as determined as ever to learn from her great-grandmother's mistakes--even if it means destroying Noah's career"--